Predicting Prosociality in Primates: Socio-Ecological Influences and a Framework of Inter-Brain Neural Synchronization - Sevastidis, Jacob; Clark, Gary; Henneberg, Maciej; Storm, Lance; Burlakoti, Arjun; Saniotis, Arthur; You, Wenpeng (Anthropological Review, 2025)
Prosocial co-operation is critical for evolution and survival on Earth and has crucially shaped the development of Homo sapiens. Inter-brain neural synchronization (IBNS) has been shown to enhance prosocial co-operation in mammals and avians. The selection pressures which led to the development of IBNS throughout primate evolution are currently unknown. This paper aims to expand the understanding of IBNS in non-human primates by reviewing the literature on various primate populations that display prosocial behaviors that could correlate with IBNS. Binary logit modelling using machine learning methods was applied to social, ecological, morphological, and biological (SEMB) variables correlated with prosocial behaviors to obtain probabilities of prosociality. Our results suggest that select SEMB variables such as daily socialisation, food-sharing and hierarchy structure are strong predictors of prosocial behaviors in primates. We provide a framework that offers testable hypotheses for the existence of IBNS in primates based on the correlations between SEMB variables and prosocial behaviors. We also offer ideas of the ecological/behavioral forces that may correlate with neural activation patterns of primate IBNS. Through comparison to Homo sapiens models, these findings suggest IBNS in primates may exist beyond cercopithecids and may be evoked by similar socio-ecological contexts. However, some key neurological distinctions between the two groups exist, influencing which distinct patterns of behavior may evoke IBNS (relative to their socio-ecological context).